«FORMAT» OF THE BODY AND THE INABILITY OF ITS REALIZATION IN THE SHORT STORY «INVALIDKA» BY MARKO CHEREMSHYNA - Horbolis L. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The article explores the body discourse in the short story "Invalidka" by Ukrainian writer of the end of the 19th and the beginning of the 20th century Marko Cheremshyna. The male and female bodies are interpreted as a key to understanding the ideological direction, thematic and problematic range, the plot and compositional specificity and the visual potential of the work. The author notes the war in the story as a main reason for the non-realization of the female and male bodies, the psychological trauma of the heroes, as well as the destruction of the family, the family, the foundations of the community.